(untitled) (TAJ: Journal of Teachers Association, 2018)
Atrial fibrillation (AF) is a common arrhythmia and a major risk factor for ischemic stroke, especially in the elderly. Patients with nonvalvular AF have a 5-fold excess risk of stroke. However, population-based data are scarce in patients who have experienced a first-ever ischemic stroke in the presence of AF regarding long-term risk of stroke recurrence and case-fatality rate. Aim of the study is to find out the outcome of ischemic stroke patients with Atrial Fibrillation. It was a descriptive type cross sectional study where 125 diagnosed cases of ischemic stroke were included. Presence of atrial fibrillation was detected by electrocardiogram. They were divided into two groups – those with atrial fibrillation and those without. Comparison was done between the two group in term of recurrence, mortality and clinical improvement. Atrial fibrillation was present in 22 (17.6%) of 125 patients with ischemic stroke. Those with AF were more frequently male, aged 45 years and older. The presence of AF was associated with high 3 months (Χ2 =4.562, df = 1, p<0.05) and 6 months mortality (Χ2 =7.868, df = 1, p<0.05), with a higher stroke recurrence rate within the first 6 months follow-up (22.7% versus 7.8% (<0.05)). At 3 months follow up clinical deterioration was noted in 9.1% patient with atrial fibrillation compared to 2.9% patients who had no arrhythmia(p<0.01) and at 6 months follow up clinical deterioration was noted in 18.2% patient with atrial fibrillation compared to 4.9% patients who had no arrhythmia(p<0.01). Ischemic stroke patients with atrial fibrillation had significant mortality within the study period compared to those without atrial fibrillation. Significant deterioration in clinical outcome was noted in atrial fibrillation group after six months. Recurrence was more in ischemic stroke patients with atrial fibrillation. Multivariate linear regression analysis shows atrial fibrillation as well as CKD, Diabetes mellitus and smoking as independent risk factor for recurrence. In conclusion, patients who had an ischemic stroke with accompanying atrial fibrillation had higher mortality, grave stroke severity, more recurrences and poorer functional status than those without atrial fibrillation. TAJ 2015; 28(2): 1-6